The Emergence of Palestinian Mughtaribûn: Diaspora Politics and State-Building in Oslo Palestine - Xavier Guignard (Mashriq & Mahjar, 2016)
This article argues that the second generation of Palestinian returnees, the mughtaribun, form a distinct category in the migratory flows that ensued from the Oslo accords. Mainly originating from North America and Western Europe, they actively took part in the state-building process while simultaneously investing in their globally-oriented professional careers. These new experts partly owe their return to the investment earmarked for these “expatriate nationals” made by the United Nations since the 1970s, endowing them with a degree of privilege in accessing political positions within the core structures of their homeland states. The mughtaribunillustrates the complex history of relation between exile and power in the Palestinian national movement and a more globalized phenomenon of circulation between highly skilled diasporic actors and their homelands.